A Faraway, Familiar Place : An Anthropologist Returns to Papua New Guinea - Smith, Michael French (Book collections on Project MUSE., 2013)
This book is for readers seeking an excursion into little-known terrain but allergic to the superficiality of some travel literature. This book explores an island village far from roads, electricity, telephone service, and the Internet, but puts to rest the cliche of "Stone Age" Papua New Guinea. The author uses his anthropological skills to illuminate Papua New Guinean lives, to nudge readers to look more closely at ideas they take for granted, and to take a wry look at his own experiences as an anthropologist. Although the author first went to Papua New Guinea in 1973, in 2008 it had been ten years since he had been back to Kragur Village, Kairiru Island, where he was an honorary "citizen." He went back not only to see people he had known for decades, but also to find out if his desire to return was more than an urge to flee the bureaucracy and recycled indoor air of his job in a large American city. The author finds in Kragur many things he remembered fondly, including a life immersed in nature and freedom from 9-5 tyranny. And he again encounters the stifling midday heat, the wet tropical sores, and the sometimes excruciating intensity of village social life that he had somehow managed to forget. Through practicing Taoist "not doing," Smith continues to learn about villagers' difficult transition from an older world based on giving to one in which money rules and the potent mix of devotion and innovation that animates Kragur's pervasive religious life. Becoming entangled in local political events, he gets a closer look at how ancestral loyalties and fear of sorcery influence hotly disputed contemporary elections. In turn, Kragur people practice their own form of anthropology on Smith, questioning him about American work, family, religion, and politics, including Barack Obama's campaign for president. They ask for help with their financial problems - accounting lessons and advice on attracting tourists - but, poor as they are, they also offer sympathy for the Americans they hear are beset by economic crisis. By the end of the book Smith returns to Kragur again - in 2011 - to complete projects begun in 2008, see Kragur's chief for the last time (he died later that year), and bring Kragur's story up to date. This book provides practical wisdom for anyone leaving well-traveled roads for muddy forest tracks and landings on obscure beaches, as well as asking important questions about wealth and poverty, democracy, and being "modern."